Optimized active layer morphology toward efficient and polymer batch insensitive organic solar cells - Kangkang Weng (Nature Portfolio, 2020)
Reliably controlling the morphology in organic solar cells is desired for up-scaling. Here Weng et al. combine the advantages of the fibril network donor and the state of the art Y6 acceptor in a two-step approach to deliver a high efficiency of 16% without batch-to-batch variation.